Analysis of growth kinetics and impact of NH3 on the morphology evolution of hexagonal-prism shaped Y4O(OH)9NO3/Y2O3 single crystals. (November 2017) - Ray, Sudeshna; Nair, Govind B.; Dhoble, S.J.; Kato, H.; Kakihana, Masato; Chen, Teng Ming
Graphical abstract: Highlights: Tailored the morphology of Y4 O(OH)9 NO3 and Y2 O3 crystals using different electrolytes by hydrothermal method. Role of NH3 in the formation of hexagonal prism like morphology. Time dependent experiments to study the growth process and formation of hexagonal prisms. Abstract: The effect of NH3 on the morphology evolution of single crystalline hexagonal-prism like Y4 O(OH)9 NO3 and Y2 O3 has been systematically investigated, as a function of reaction time, by using a combination of powder X-ray diffraction (XRD) and scanning electron microscopy (SEM). Rational control over the morphology has been achieved by the choice of suitable electrolytes like NaNO3, KNO3, NH4 NO3, KCl and NH4 Cl in the presence of NH4 OH. We report that the cross-sectional geometry of hydrothermally grown one-dimensional Y4 O(OH)9 NO3 crystals can be tuned from spherical to hexagonal-prism like shape by introducing a particular reagent like NH4 NO3 in the presence of NH4 OH. An 'oriented attachment' mediated growth process takes place along with the 'dissolution-recrystallization' route which eventually resulted in the generation of the single crystals with hexagonal-prism like morphology.